Development A Fire Extinguisher Nozzle Drive Mechanism with Android Monitoring and Control - Cahya Kusuma; Vega Indra Citra Utama; Wawan Kusdiana; Aris Tri Ika R (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The warehouses on land are rooms that are prone to fire hazards. The Spare Parts warehouse contains engine spare parts, rubber lifeboats, ship paint, thinner, maritime equipment, lubricating oil, dry food, and other logistics support. These materials have a high level of vulnerability to fire hazards. Thus, the danger of fire is one of the potential threats that can occur in Dismatbek. A fire protection system is needed that can minimize losses due to fire. This research is intended to develop a design for a fire extinguisher nozzle drive mechanism with Android monitoring and control. By building a mechanical movement mechanism for the nozzle in the vertical and horizontal directions so that the focus can be directed to the fire source with the Esp 32 Microcontroller. There is a monitoring and control unit via an Android smartphone which is equipped with three sensors, namely fire, temperature, and smoke sensors which are connected to an Arduino microcontroller to identify fire hazards. From the overall test results, it was found that the nozzle was successful in moving vertically and horizontally with a good mechanism for driving the fire nozzle arm in transmitting the power distributed to the nozzle arm resulting in a gear ratio of 2.06: 1 with a final rotational speed of 3.8 rpm at In the elevation direction, the torque is 1,606 Nm and in the azimuth direction, the speed is 7.28 rpm, the final torque is 3,028 Nm. The fire nozzle monitoring and control unit is capable of detecting potential fire hazards and the nozzle can be controlled with an Android smartphone and can extinguish fires by spraying water at the source of the fire well.